Information Provision and Preparatory Interventions: Shaping the Lens for Children's Understanding and Response to Painful Contexts - Tiina Jaaniste (MDPI AG, 2021)
Any painful or medical experience that we face is viewed from the lens with which we understand and view the experience [...]